" PENGARUH ZAT PENGATUR TUMBUH ALAMI DAN SINTETIK TERHADAP PERTUMBUHAN BIBIT DURIAN ( Durio zibethinus murr) HASIL SAMBUNG" - satria, ary (Jurnal Embrio, 2024)
The research aims to obtain the best natural and synthetic ZPT for the growth of grafted durian (Durio zibethinus murr) seedlings. The experiment was carried out in Aie Pacah, Koto Tangah District, Padang City, West Sumatra at an altitude of 25 meters above sea level, at the Laboratory of the Faculty of Agriculture, Tamansiswa University, Padang and the Physiology Laboratory, Andalas University, Padang from June to September 2023. The experiment used a completely randomized design with no treatment ZPT, Shallot Extract, Coconut Water, Bamboo Shoots, Atonik, Hantu. Each treatment was repeated 4 times, 1 treatment contained 5 samples for a total of 120 experiments. The results of the treatment showed that giving 2 ml/l synthetic and natural growth regulators the best treatment was obtained from giving natural growth regulators for bamboo shoots and Atonik synthetic ZPT. It can be seen from the results of natural ZPT treatment of bamboo shoots and atonic synthetic ZPT that it can increase the growth and development of durian seedlings compared to other treatments in the observation parameters: number of leaves, root length, root wet weight and root dry weight.